Structural Insights from the NMR Spectroscopy of Quadrupolar Nuclei: Exploiting Electric Field Gradient and Spin-Spin Coupling Tensors - Perras, Frédéric Alain (Université d'Ottawa / University of Ottawa, 2015)
NMR spectroscopy has evolved into one of the most important characterization techniques in chemistry with which it is possible to obtain valuable structural, dynamical, and mechanistic information. Most applications of NMR have however been limited to the use of nuclei having spin quantum numbers of 1/2. This thesis discusses the developments that have been advanced in order to extract quantitative structural information from the NMR spectroscopy of quadrupolar nuclei (spin, I>1/2) which account for the vast majority of the NMR-active nuclei. In a first part of the thesis, a NMR crystallographic method is developed which uses the electric field gradient tensor measured at the nuclear sites as an experimental constraint in DFT-based crystal structure refinements. This inclusion of experimental data into crystal structure refinements enables the determination of higher quality, and experimentally-relevant, structures. We apply this new methodology in order to determine higher quality crystal structures for the non-linear optical material Na2B2Al2O7, sodium pyrophosphates, and the near-zero thermal expansion material ZrMgMo3O12. In a second part of this thesis, experimental techniques are developed for the measurement of spin-spin coupling between pairs of quadrupolar nuclei; the measurement of spin-spin coupling carries with it extremely valuable distance and connectivity information. Using DOR NMR, heteronuclear residual dipolar coupling as well as homonuclear J coupling multiplets can be observed. Notably, the J coupling between quadrupolar nuclei can still be measured in A2 spin systems, unlike in the case of pairs of spin-1/2 nuclei. The theory that was developed for the characterization of these multiplets was extended for the general simulation of exact NMR spectra of quadrupolar. This program, known as QUEST, is now free to use by anyone in the scientific community. Pulsed J-resolved NMR experiments are then described which enable the facile measurement of J and dipolar coupling in homonuclear pairs of quadrupolar nuclei. Notably, the J splitting is greatly amplified in A2 spin systems which provides strong structural information and enables the precise detection of smaller J coupling constants. These techniques are applied towards directly studying gallium metal-metal bonding interactions as well as boron-boron bonds in diboron compounds of importance in β-boration chemistry.
Keywords: NMR Spectroscopy; Structure Solution; Quadrupolar Nuclei; Spin-Spin Coupling